Determinación de la evapotranspiración potencial y precipitación efectiva del cantón Zapotillo, para mejorar la toma de decisión en cuanto a los requerimientos hídricos de los cultivos - González Armijos, Juan Andrés (2024)
In order to guarantee food security, it is essential to take advantage of available water resources. Therefore, it is essential to have evapotranspiration data to properly meet the water needs of crops, therefore, this research was carried out in Zapotillo canton, belonging to Loja province, in which data of potential evapotranspiration (ETo) and effective precipitation (Pe) were determined, to carry out the research data provided by INAMHI-SENAMHI and the satellite database Chelsa Climate were used. The methodology consisted of selecting the meteorological stations with the greatest incidence in the study area, then the collection, tabulation and filling in of missing data of the climatic variables necessary to determine ETo and Pe, two methods were used to determine the potential evapotranspiration; The simplified Hargreaves and modified Penman Monteih methods were used to determine potential evapotranspiration. In addition, effective precipitation was determined using the USDA Soil Conservations Service method, developed by the USCS, and finally, a correlation factor was calculated from the ETo data obtained from the INAMHI-SENAMHI database. As an additional contribution, representative maps of maximum, average and minimum temperature, precipitation, potential evapotranspiration and effective precipitation were generated for the Zapotillo canton, which will be of great use to the interested population.